Psychological distress and quality of life in Chinese early-stage breast cancer patients throughout chemotherapy - Bo Lan; Dan Lv; Min Yang; Xiaoying Sun; Li Zhang; Fei Ma (Journal of the National Cancer Center, 2022)
Background: Breast cancer survivors with psychological problems have higher mortality than those without. Therefore, it is important to monitor and manage their psychological status. This study mainly aimed to dynamically estimate the prevalence of anxiety and depression and to clarify the factors associated with anxiety and depression of patients undergoing adjuvant chemotherapy. The secondary objective was to investigate the relationship between depression and anxiety and quality of life (QOL) in Chinese early-stage breast cancer patients. Methods: In a prospective observational single-center cohort study with early-stage breast cancer patients (n = 290), depression and anxiety severity, QOL, and social support were measured using the Hospital Anxiety and Depression Scale (HADS), the Functional Assessment of Cancer Therapy-Breast Cancer (FACT-B) scale, and the Chinese version of the Social Support Rating Scale (SSRS), respectively. Canonical correlations were applied to identify correlates between anxiety and depression and demographic and clinical variables. One-way repeated measure analysis of covariance (RMANCOVA) was used to analyze dynamic changes in anxiety, depression, and QOL. Relationships between anxiety and depression and QOL were analyzed using two-way RMANCOVA. Results: The overall anxiety and depression prevalence rates were 35.2% and 44.1%, respectively. Age (P = 0.042), surgical method (P = 0.009), social support (P = 0.001), and breast cancer family history (P = 0.045) were significantly associated with depression. The number of children (P = 0.048) was significantly associated with anxiety. FACT-B scores differed between anxiety and depression and nonanxiety and depression groups, and patients with higher HADS depression and anxiety scores had lower FACT-B scores during chemotherapy (P < 0.001). Conclusions: We observed dynamic changes in anxiety and depression and QOL and associated factors of anxiety and depression. These findings can provide guidance for psychological monitoring and support for breast cancer patients during the postoperative chemotherapy period.